The Relationship Between Cognitive Styles and Young Adult Learners' Preferences for Written Corrective Feedback - Negar Moslemi; Adel Dastgoshadeh (Asociación Colombiana de Profesores de Ingles, 2017)
This study aimed to investigate the relationship between learners' cognitive styles and their preferences for different types and frequencies of written corrective feedback and for different types of errors to be corrected. Data were collected from 60 English as a foreign language learners at intermediate and upper-intermediate levels. The instruments included the Ehrman and Leaver Learning Styles Questionnaire, and a questionnaire constructed by Amrhein and Nassaji (2010). The results indicated that there is a strong relationship between learners' cognitive styles and their preferences for a particular type of written corrective feedback and for different types of errors to be corrected; but there is no significant relationship between cognitive styles and learners' preferences for frequencies of written corrective feedback.